Streamer-to-spark transition initiated by a nanosecond overvoltage pulsed discharge in air. (17th March 2017) - Lo, A; Cessou, A; Lacour, C; Lecordier, B; Boubert, P; Xu, D A; Laux, C O; Vervisch, P
Abstract: This study is focused on the streamer-to-spark transition generated by an overvoltage nanosecond pulsed discharge under atmospheric pressure air in order to provide a quantitative insight into plasma-assisted ignition. The discharge is generated in atmospheric pressure air by the application of a positive high voltage pulse of 35 kV to pin-to-pin electrodes and a rise time of 5 ns. The generated discharge consists of a streamer phase with high voltage and high current followed by a spark phase characterized by a low voltage and a decreasing current in several hundreds of nanosecond. During the streamer phase, the gas temperature measured by optical emission spectroscopy related to the second positive system of nitrogen shows an ultra-fast gas heating up to 1200 K at 15 ns after the current rise. This ultra-fast gas heating, due to the quenching of electronically excited species by oxygen molecules, is followed by a quick dissociation of molecules and then the discharge transition to a spark. At this transition, the discharge contracts toward the channel axis and evolves into a highly conducting thin column. The spark phase is characterized by a high degree of ionization of nitrogen and oxygen atoms shown by the electron number density and temperature measured from optical emission spectroscopy measurements of N + lines. Schlieren imaging and optical emission spectroscopy techniques provide the time evolution of the spark radius, from which the initial pressure in the spark is estimated. The expansion of the plasma is adiabatic in the early phase. The electronic temperature and density during this phase allows the determination of the isentropic coefficient. The value around 1.2–1.3 is coherent with the high ionization rate of the plasma in the early phase. The results obtained in this study provide a database and the initial conditions for the validation of numerical simulations of the ignition by plasma discharge.